Math wonders to inspire teachers and students - Posamentier, Alfred S. (Alexandria : Association for Supervision and Curriculum Development, 2003)
A veteran teacher provides examples of the beauty and wonder of numbers and mathematics that are guaranteed to get student sand teachers more interested in math.
Keywords: Mathematics -- Study and teaching; Mathematical recreations